COMPLICATIONS AFTER HEPATECTOMY - Claudemiro Quireze Junior; Fabricio Ferreira Coelho; Agnaldo Soares Lima; Hugo Pinto Marques; Martin Palavecino; Timothy Pawlik; Rene Adam; Olivier Soubrane; Paulo Herman; Ricardo Lemos Cotta-Pereira (ABCD: Arquivos Brasileiros de Cirurgia Digestiva)
ABSTRACT Complete removal of metastatic disease and maintenance of an adequate liver remnant remains the only treatment option with curative intent concerning colorectal liver metastases. Surgery impacts on the long-term prognosis and complications adversely affect oncological results. The actual morbidity involving this scenario is debatable and estimated to be ranging from 15% to 50%. Postoperative complications eventually lead to an increase in both mortality rates and tumor recurrence. Biliary fistula and liver failure are the leading complications following liver resection to metastatic colorectal cancer. Prophylactic drainage does not prevent fistulas or hemorrhage. Drainage along with endoscopic intervention and/or surgery may be necessary for grade B and C fistulas. Liver failure is a potentially lethal complication with few therapeutic options. Patient selection and preoperative care are crucial for its prevention.